2015
DOI: 10.1111/jsm.12725
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Prevalence Rates of Sexual Difficulties, Sexual Dysfunctions, and Sexual Distress in Heterosexual Women: Results from an Online Survey in Flanders

Abstract: Introduction Although age-related prevalence rates of female sexual difficulties, i.e., difficulties with sexual desire, arousal, orgasm, or pain have occasionally been studied—with mostly inconsistent results—the age-related prevalence rates of female sexual dysfunctions, i.e., sexual difficulties that are associated with sexual distress, have not. Moreover, the association of age with sexual distress, i.e., distress due to sexual difficulties, has almost completely been neglected in epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 21 publications
3
27
1
Order By: Relevance
“…For example, a study by Jiann et al 26 found that although overall rates of sexual dysfunction were higher for older women owing to lower desire, arousal, and lubrication, sexual satisfaction was actually highest in this same age group. Similarly, Hendrickx et al 27 found that although sexual difficulties and sexual dysfunctions increase with age, sexual distress was actually more common in younger women. Our study did not include a significant number of women at the menopausal transition and therefore there is large variance in the results for those women near menopause.…”
Section: Discussionmentioning
confidence: 89%
“…For example, a study by Jiann et al 26 found that although overall rates of sexual dysfunction were higher for older women owing to lower desire, arousal, and lubrication, sexual satisfaction was actually highest in this same age group. Similarly, Hendrickx et al 27 found that although sexual difficulties and sexual dysfunctions increase with age, sexual distress was actually more common in younger women. Our study did not include a significant number of women at the menopausal transition and therefore there is large variance in the results for those women near menopause.…”
Section: Discussionmentioning
confidence: 89%
“…In the studies that have assessed distress about sexual problems, a consistent finding has been that for most sexual difficulties, distress is less commonly reported in older women compared with younger women (Hayes & Dennerstein, 2005;Hendrickx et al, 2015;Mitchell et al, 2013). For example, in the U.K. Natsal-3 survey, 9.5% of women aged 65-74 reported being "distressed or worried" about their sex life, compared with 12.7% of women aged 45-54 years.…”
Section: Aging Women's Sexual Problemsmentioning
confidence: 92%
“…For example, in the U.K. Natsal-3 survey, 9.5% of women aged 65-74 reported being "distressed or worried" about their sex life, compared with 12.7% of women aged 45-54 years. Hendrickx et al (2015) reported that sexual distress was more common in younger women than in older women in their sample of 15,048 heterosexual women aged 16-74 years living in Flanders. With the exception of sexual difficulties, dyspareunia and lubrication difficulties, sexual symptoms were positively associated with age.…”
Section: Aging Women's Sexual Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies conducted in the Great Britain [19] and Flanders, Belgium [20] seek to address some of these gaps, assessing sexual functioning in larger samples of the general population. While the Flanders study reports age-specific prevalence of sexual difficulties and associated distress, the study draws inferences from a convenience sample of the population (online survey advertised through media channels), which raises concern regarding the generalizability of their findings [20].…”
Section: Introductionmentioning
confidence: 99%